Motor Third-Party Liability Insurance in Developing Countries : Raising Awareness and Improving Safety - Gönülal, Serap O. (World Bank, Washington, DC, 2013)
This study focusses on motor insurance, possibly the most important type of insurance sold in developing countries. In most countries, motor third-party liability (MTPL) insurance is compulsory in order to protect the public. World Bank studies in Africa, Central Asia, and Europe have shown that motor insurance premiums represent at least 30 percent of all non-life premium income. MTPL insurance has been introduced in the formerly centrally planned economies only in the past decade, and it is poorly understood. Motorists are inclined to view it as a form of tax that they are at liberty to evade, rather than as a protection against their personal liability, a concept that is not familiar to the general public. This report discusses the high motor accident casualty rate in developing countries, and predicts that it will increase dramatically by 2020. It focuses specific aspects of MTPL systems, with reference to the experiences gained in both developed and developing markets. The report examines existing practices, and discusses some aspects of the MTPL system, referring especially to the experiences of Brazil, which sought to correct uninsured vehicle rates that were as high as 60 percent or more. The study concludes with results from the experiences of the countries studies, and outlines some important features to guide future work in those countries. It underlines the importance of MTPL insurance for road safety, personal responsibility, and secure traffic systems in developing countries.